2023
DOI: 10.3390/ijms24021361
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Management of High-Grade Chondrosarcoma: An Update on Targets and Treatment Options

Abstract: This review provides an overview of histopathology, clinical presentation, molecular pathways, and potential new systemic treatments of high-grade chondrosarcomas (CS), including grade 2–3 conventional, dedifferentiated, and mesenchymal CS. The diagnosis of CS combines radiological and histological data in conjunction with patient clinical presentations. Conventional CS is the most frequent subtype of CS (85%) and represents about 25% of primary bone tumors in adults; they can be categorized according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Developing an efficient treatment strategy requires a better understanding of the molecular survival pathways involved in chondrosarcomas and their chemotherapy and radiation resistance mechanisms [ 104 ]. Chondrosarcoma subtypes differ at the molecular genetic level ( Table 2 ) [ 105 ]. Recent studies have suggested several promising biomarkers and therapeutic targets for chondrosarcomas, with better understanding of chondrosarcoma genomic alterations and biology [ 103 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Targets and Novel Treatment Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Developing an efficient treatment strategy requires a better understanding of the molecular survival pathways involved in chondrosarcomas and their chemotherapy and radiation resistance mechanisms [ 104 ]. Chondrosarcoma subtypes differ at the molecular genetic level ( Table 2 ) [ 105 ]. Recent studies have suggested several promising biomarkers and therapeutic targets for chondrosarcomas, with better understanding of chondrosarcoma genomic alterations and biology [ 103 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Targets and Novel Treatment Optionsmentioning
confidence: 99%
“…Chondrosarcoma subtypes differ at the molecular genetic level ( Table 2 ) [ 105 ]. Recent studies have suggested several promising biomarkers and therapeutic targets for chondrosarcomas, with better understanding of chondrosarcoma genomic alterations and biology [ 103 , 105 , 106 , 107 , 108 , 109 , 110 ]. As shown in Table 2 , the signaling pathways underpinning chondrosarcoma genesis such as IDH1/2 mutations, CDKN2A/B deletions, and TP53 mutations can be potential therapeutic targets [ 105 ].…”
Section: Targets and Novel Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of these factors, independently of O2 concentrations, will be responsible for tumor progression and radioresistance. In addition, chondrosarcoma cells are often EXT1/2 mutated and CDKN2A/B deletions are also frequent, as well as COL2A1 mutations [ 27 ]. In osteosarcoma, another rare malignant bone tumor, the expression of several repetitive elements was observed differentially expressed with normal bone.…”
Section: Introductionmentioning
confidence: 99%